Upcycling of PET oligomers from chemical recycling processes to PHA by microbial co-cultivation - Liu, Pan; Zheng, Yi; Yuan, Yingbo; Han, Yuanfei; Su, Tianyuan; Qi, Qingsheng (Waste management (Elmsford), 2023)
[Display omitted] •Upcycling of PET oligomers to PHA is viable by microbial co-cultivation.•PET hydrolase LCCICCG was secreted using Escherichia coli BL21.•LCCICCG depolymerized PET oligomers into monomers during the fermentation process.•Engineered Pseudomonas putida KT2440 to synthesize PHA from PET monomers.•Revealed the collaboration of strains in co-cultivation by fluorescence labeling. Polyethylene terephthalate (PET) is the most widely consumed polyester plastic and can be recycled by many chemical processes, of which glycolysis is most cost-effective and commercially viable. However, PET glycolysis produces oligomers due to incomplete depolymerization, which are undesirable by-products and require proper disposal. In this study, the PET oligomers from chemical recycling processes were completely bio-depolymerized into monomers and then used for the biosynthesis of biodegradable plastics polyhydroxyalkanoates (PHA) by co-cultivation of two engineered microorganisms Escherichia coli BL21 (DE3)-LCCICCG and Pseudomonas putida KT2440-ΔRDt-ΔZP46C-M. E. coli BL21 (DE3)-LCCICCG was used to secrete the PET hydrolase LCCICCG into the medium to directly depolymerize PET oligomers. P. putida KT2440-ΔRDt-ΔZP46C-M that mastered the metabolism of aromatic compounds was engineered to accelerate the hydrolysis of intermediate products mono-2-(hydroxyethyl) terephthalate (MHET) by expressing IsMHETase, and biosynthesize PHA using ultimate products terephthalate and ethylene glycol depolymerized from the PET oligomers. The population ratios of the two microorganisms during the co-cultivation were characterized by fluorescent reporter system, and revealed the collaboration of the two microorganisms to bio-depolymerize and bioconversion of PET oligomers in a single process. This study provides a biological strategy for the upcycling of PET oligomers and promotes the plastic circular economy.